The Role of Prices Relative to Supplemental Benefits and Service Quality in Health Plan Choice. Issue 2 (8th December 2017) - Bünnings, Christian; Schmitz, Hendrik; Tauchmann, Harald; Ziebarth, Nicolas R.
Abstract: This article links representative enrollee panel data to health plan data on (1) prices, (2) service quality, and (3) nonessential benefits for the German statutory multipayer market and the years 2007–2010. We first show that although heavy federal regulation ensures a simple choice architecture, the majority of health plans are dominated—even when considering four nonprice attributes. Enrollees in dominated plans are older, less educated, and unhealthier. Second, we assess how switchers value prices relative to nonprice health plan attributes. Our mixed logit models incorporate a total of 1, 700 health plan choices with each more than 50 choice sets. While prices are an important determinant for nearly everyone, 40 percent of all switchers do not seem to value service quality and supplemental benefits when choosing health plans.